Correlation of hepatitis B surface antigen level with response to telbivudine in naive patients with chronic hepatitis B. Issue 2 (10th May 2013) - Li, Xuefen; Wang, Yiyin; Han, Dongsheng; Zhang, Wen; Zhang, Zike; Ye, Xianfei; Tian, Li; Dong, Yuejiao; Zhu, Qiaoyun; Chen, Yu
<x xml:space="preserve">Abstract</x> Aim Hepatitis B surface antigen (HBsAg) has become a marker to judge immunological response to hepatitis B therapy. Quantified serum HBsAg levels can predict the response to pegylated interferon and entecavir. In this study, we aimed to explore the correlation of serum HBsAg levels with response to telbivudine (LdT) treatment in patients with chronic hepatitis B (CHB). Methods Seventy‐three treatment‐naive CHB patients were recruited and received LdT monotherapy for 52 weeks and serial HBsAg levels were measured at five protocol time points. According to therapeutic efficacy at week 52, three subgroups of patients were identified, including complete responders (CR), partial responders (PR) and non‐responders (NR). Results After 52 weeks of treatment, CR, PR and NR represented 19 (26%), 33 (45%) and 21 (29%) patients in the sample of 73, respectively. The median values of baseline HBsAg (log10 IU/mL) were 4.05, 4.50 and 5.03 for CR, PR and NR, respectively. There was a distinct decline of HBsAg at week 52; median log10 HBsAg levels (IU/mL) were 3.61 (CR), 3.86 (PR) and 4.31 (NR). Positive correlation between HBsAg levels and HBV DNA loads was observed in the group of NR and early antiviral treatment of PR, but not in CR. Conclusion Initial HBsAg level was closely correlated with the efficacy of LdT. Patients with low HBsAg levels presented satisfactory responses. Therefore, initial level and correlation with HBV DNA of the serum HBsAg levels could predict responsiveness in CHB patients receiving LdT.